An Evaluation of the Precision of Measurement of Ryff’s Psychological Well-Being Scales in a Population Sample - Abbott, Rosemary A. (Springer Netherlands, 2009)
The aim of this study is to assess the effective measurement range of Ryff’s Psychological Well-being scales (PWB). It applies normal ogive item response theory (IRT) methodology using factor analysis procedures for ordinal data based on a limited information estimation approach. The data come from a sample of 1,179 women participating in a midlife follow-up of a national birth cohort study in the UK. The PWB scales incorporate six dimensions: autonomy, positive relations with others, environmental mastery, personal growth, purpose in life and self-acceptance. Scale information functions were calculated to derive standard errors of measurement for estimated scores on each dimension. Construct variance was distinguished from method variance by inclusion of method factors from item wording (positive versus negative). Our IRT analysis revealed that the PWB measures well-being most accurately in the middle range of the score distribution, i.e. for women with average well-being. Score precision diminished at higher levels of well-being, and low well-being was measured more reliably than high well-being. A second-order well-being factor loaded by four of the dimensions achieved higher measurement precision and greater score accuracy across a wider range than any individual dimension. Future development of well-being scales should be designed to include items that are able to discriminate at high levels of well-being.